The Association Between Sociodemographic Factors, Onset and Duration of Ilness With Personal and Social Performances in Outpatient Chronic Schizophrenia in Stabilization Phase - Alyya Andini Syafitri; Vita Camellia; M. Yusuf Rachmatsyah; Riri Andri Muzasti (Faculty of Medicine, Universitas Airlangga, 2025)
Introductions: Schizophrenia is a serious mental illness that affects a person’s daily quality of life. Various factors such as sociodemographic factors, onset, and duration of illness can be related to the quality of life in schizophrenia. The parameter for measuring quality of life in schizophrenia patients is the Personal and Social Performance Scale (PSP Scale). This study is aim to analyze the association between sociodemographic factors, onset, and duration of illness in outpatient chronic schizophrenia patients in the stabilization phase with their personal and social performances. Methods: This study is an observational analytical research with a cross-sectional study design. The sample of this study was outpatient chronic schizophrenia stabilization phase in a mental hospital of North Sumatra Province, Prof. Dr. Muhammad Ildrem Medan Mental Hospital and selected using the purposive sampling method, where after calculating using the multivariate analysis predictive concept method, the number of samples needed was 80 samples. The data used is primary data obtained directly from respondents. The analysis used is univariate, bivariate and multivariate analysis with chi-square. Results: There is a significant relationship between the level of personal and social function with education level (p=0.002), marital status (p=0.001), and employment (p=0.002) in outpatient chronic schizophrenia stabilization phase. Conclusion: The results of multivariate analysis showed that the most significant variables with personal and social function in outpatient chronic schizophrenia stabilization phase were marital status (OR=4.395), employment (OR=4.220), and education level (OR= 0.220) in order of the variables with the greatest strength of influence.